Detection of Toxocara cati from Fecal Samples of Domestic Pet Cats at Pet Clinic Surabaya and Durability of Toxocara cati Eggs with In Vitro Media - O. R. P. A. Nussa; A. Kurnianto; I. P. Hermawan (Universitas Bengkulu, 2021)
The purpose of this study was to determine the presence of Toxocara cati eggs in the feces of Domestic pet cats at the Surabaya Animal Clinic and the durability of Toxocara cati eggs with in vitro media. Total fecal samples taken were 30 cat feces from 5 animal clinics in Surabaya, then detected Toxocara cati eggs using an enlargement microscope 100 times, followed by counting eggs per gram of feces. The eggs used were approximately 200 eggs in each petri dish, then positive feces of Toxocara cati with various in vitro media using 0.9% NaCl, 1% PBS and 1% CMC for 24 hours and 48 hours. The results showed that two fecal samples positive Toxocara cati from 30 samples fecal and durability Toxocara cati eggs on medium in vitro over 24 showed 28% NaCl; PBS 68%; CMC 5% and at 48 hours showed 23.7% NaCl; PBS 58%; CMC 17.3%. Based on these results, the conclusion is two fecal (6,67 %) positive T.cati from 30 fecal samples, and the best medium in the test of the durability of Toxocara cati egg is 1% PBS.